Cigarette smoke exposure during pregnancy alters fetomaternal cell trafficking leading to retention of microchimeric cells in the maternal lung. - Anja Vogelgesang; Cristina Scapin; Caroline Barone; Elaine Tam; Anna Blumental Perry; Christiane E L Dammann (PLoS ONE, 2014)
Cigarette smoke exposure causes chronic oxidative lung damage. During pregnancy, fetal microchimeric cells traffic to the mother. Their numbers are increased at the site of acute injury. We hypothesized that milder chronic diffuse smoke injury would attract fetal cells to maternal lungs. We used a green-fluorescent-protein (GFP) mouse model to study the effects of cigarette smoke exposure on fetomaternal cell trafficking. Wild-type female mice were exposed to cigarette smoke for about 4 weeks and bred with homozygote GFP males. Cigarette smoke exposure continued until lungs were harvested and analyzed. Exposure to cigarette smoke led to macrophage accumulation in the maternal lung and significantly lower fetal weights. Cigarette smoke exposure influenced fetomaternal cell trafficking. It was associated with retention of GFP-positive fetal cells in the maternal lung and a significant reduction of fetal cells in maternal livers at gestational day 18, when fetomaternal cell trafficking peaks in the mouse model. Cells quickly clear postpartum, leaving only a few, difficult to detect, persisting microchimeric cells behind. In our study, we confirmed the postpartum clearance of cells in the maternal lungs, with no significant difference in both groups. We conclude that in the mouse model, cigarette smoke exposure during pregnancy leads to a retention of fetal microchimeric cells in the maternal lung, the site of injury. Further studies will be needed to elucidate the effect of cigarette smoke exposure on the phenotypic characteristics and function of these fetal microchimeric cells, and confirm its course in cigarette smoke exposure in humans.